2023
DOI: 10.7759/cureus.38357
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Variants in Patients With Microcytic Hypochromic Anemia: A Review of Indian Studies

Abstract: Microcytic hypochromic (MCHC) anemia with hemolytic components is common in clinical practice. Hemoglobinopathies and variants are one of the important underlying causes of MCHC anemia. The Indian population, by large, as various studies reported, showed a plethora of hemoglobinopathies with regional predilections for its types. The present systematic review is carried out for the evaluation of MCHC anemia for its underlying causes of hemoglobinopathies and their loco regional comparisons. The review was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The evaluation of haemoglobin abnormalities in the form of characteristics and diseases is advised for all paediatric patients with refractory anaemia. 15 F Afshin et al (2021) did a study to concluded that the examination of Hb Bart's and Hb H are direct approaches for the diagnosis of thalassemia, however only a few cases of thalassemia were found in this study, and the most of them were missed. Because of this, -thalassemia must be confirmed in Hb Bart's newborns, and molecular investigation is required to count the number of defective genes.…”
Section: Study Statusmentioning
confidence: 56%
See 1 more Smart Citation
“…The evaluation of haemoglobin abnormalities in the form of characteristics and diseases is advised for all paediatric patients with refractory anaemia. 15 F Afshin et al (2021) did a study to concluded that the examination of Hb Bart's and Hb H are direct approaches for the diagnosis of thalassemia, however only a few cases of thalassemia were found in this study, and the most of them were missed. Because of this, -thalassemia must be confirmed in Hb Bart's newborns, and molecular investigation is required to count the number of defective genes.…”
Section: Study Statusmentioning
confidence: 56%
“…13 Kamran DS et al (2023) did a study to concluded that peripheral smear can be used in high-risk locations and, although though it is not a very sensitive tool for screening for the Sickle trait, it can be supported by more advanced methods in ambiguous circumstances. 14 Kharche K et al(2023) did a study to concluded that in order to treat microcytic hypochromic anaemia with a hemolytic component that is resistant to treatment, a systematic review of 14 research from four regions and across India was conducted. The rare haemoglobin variations that the electrophoresis was unable to identify are likely best discovered by the HPLC.…”
Section: Study Statusmentioning
confidence: 99%
“…Using a preprogrammed buffer gradient that raises the ionic strength depending on ionic interactions to the analytical cartridge, hemoglobin is separated from the analytical cartridge by cation-exchange HPLC [16]. More samples can be processed faster and with fewer technicians due to the HPLC's automation.…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Pan India surveillance and the systematic review carried by Kharche K, Bhake over 14 studies across four regions revealed that hemoglobinopathies must be analyzed in microcytic hypochromic anemia with a hemolytic component that is resistant to treatment. The HPLC is likely the best analyzer for finding the rare hemoglobin variants that the electrophoresis was unable to find [16]. Hbs A, A2, F, S, C, and D Punjab and G Philadelphia usually remain different from each other.…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%